Head motion during MRI acquisition reduces gray matter volume and thickness estimates - Reuter, Martin; Tisdall, M. Dylan; Qureshi, Abid; Buckner, Randy L.; van der Kouwe, André J.W.; Fischl, Bruce (NeuroImage (Orlando, Fla.), 2015)
Imaging biomarkers derived from magnetic resonance imaging (MRI) data are used to quantify normal development, disease, and the effects of disease-modifying therapies. However, motion during image acquisition introduces image artifacts that, in turn, affect derived markers. A systematic effect can be problematic since factors of interest like age, disease, and treatment are often correlated with both a structural change and the amount of head motion in the scanner, confounding the ability to distinguish biology from artifact. Here we evaluate the effect of head motion during image acquisition on morphometric estimates of structures in the human brain using several popular image analysis software packages (FreeSurfer 5.3, VBM8 SPM, and FSL Siena 5.0.7). Within-session repeated T1-weighted MRIs were collected on 12 healthy volunteers while performing different motion tasks, including two still scans. We show that volume and thickness estimates of the cortical gray matter are biased by head motion with an average apparent volume loss of roughly 0.7%/mm/min of subject motion. Effects vary across regions and remain significant after excluding scans that fail a rigorous quality check. In view of these results, the interpretation of reported morphometric effects of movement disorders or other conditions with increased motion tendency may need to be revisited: effects may be overestimated when not controlling for head motion. Furthermore, drug studies with hypnotic, sedative, tranquilizing, or neuromuscular-blocking substances may contain spurious “effects” of reduced atrophy or brain growth simply because they affect motion distinct from true effects of the disease or therapeutic process. •MRI head motion induces a consistent bias in morphometric analysis.•Increased motion generally causes smaller gray matter volume and cortical thickness estimates.•Effects of movement disorders may be severely overestimated when not controlling for head motion.•Drugs that inhibit motion likely provide a spurious effect of reduced atrophy rates.•Exclusion of scans that fail a visual quality check is not sufficient to remove this bias.